INTERPROFESSIONAL COMMUNICATION AND JOB SATISFACTION: A CROSS-SECTIONAL STUDY AMONG HEALTHCARE ASSISTANTS AND TECHNICIANS IN SAUDI ARABIA - Mohammed Asi Alanazi, Hammad Jarad Al-Shammari, Fahd Mufarreh Al-Mutairi, Hasah Menahi Mohammed Abushwairbat,; Amnah Abdullh Aljmeeli, Ahmad Masair Dhisan Aljameeli, Ahoud Gharbi Aldhafeeri, Mohamad Abdullah Falah Alshamri, (Chelonian Research Foundation, 2022)
Effective interprofessional communication is crucial for the delivery of high-quality healthcare services and the satisfaction of healthcare professionals. This cross-sectional study aimed to investigate the relationship between interprofessional communication and job satisfaction among healthcare assistants and technicians in Saudi Arabia. A sample of 432 healthcare professionals (272 females, 160 males) from various disciplines (pharmacy technicians, nursing technicians, nursing health assistants, and healthy assistants) in three regions of Saudi Arabia (Riyadh, Jeddah, and Dammam) completed a survey questionnaire assessing their perceptions of interprofessional communication and job satisfaction. The data were analyzed using descriptive statistics, independent samples t-tests, one-way ANOVA, and multiple regression analysis. The results showed significant differences in the perceptions of interprofessional communication and job satisfaction across healthcare roles and regions. Interprofessional communication was a significant predictor of job satisfaction, controlling for demographic and work experience variables. The qualitative analysis of open-ended questions revealed themes related to the benefits, barriers, and strategies for improving interprofessional communication and job satisfaction. The findings highlight the importance of fostering effective interprofessional communication to promote job satisfaction and quality care among healthcare assistants and technicians in Saudi Arabia.